Polish Managers’ Leadership Styles: Developing and Validating the Managerial Styles of a Leading Questionnaire - Babiak, Jolanta (Department of Psychology, University of Wrocław, 2014)
This article develops a new measure for assessing leadership styles. A six-factor solution was identified in exploratory factor analysis (n = 139) and then was verified in confirmatory factor analysis (n = 477). The final questionnaire encompasses 51 items grouped into six dimensions: structuring, autocratic, participative, Machiavellian, rewarding, and distant. The scales’ internal consistency range from.61 to.79. Internal validity was initially supported by intercorrelations among six leadership styles. External validity was verified through correlation analysis between leadership styles and personality traits of the Costa & McCrae (1995) five-factor model.
Keywords: factor analysis; questionnaire development; managerial behaviours; leadership styles